Budidaya Kangkung dan Ikan Lele Dengan Sistem Aquaponik di Kelurahan Tobekgodang - Iskandar Putra; Abrar Bayu Samudra; Artharisa Julia Hamdany; Dwi Pungga Rahmayani; Muhammad Alvi Syahrin; Nurul Fadilah; Raka Aditya Pratama; Silqi Khanifah; Tassya Monica; Tiyah Fadhilah (Dirkantara Indonesia, 2023)
These kale and catfish plants can be developed into aquaponic cultivation. Aquaponics is the concept of developing a bio-integrated farming system, which is a series of technologies that combines aquaculture techniques and hydroponic farming techniques. Where fish farming waste is in the form of metabolic waste and leftover feed used as nutrients for plants. Thus, research can be carried out that aims to find out how to cultivate water spinach and catfish using an aquaponics system to take advantage of minimally sized vacant land. The methods applied in aquaponic cultivation are the manufacture of aquaponic growing media, aquaponics maintenance and care, and the process of harvesting kale. The resulting kale plants have different growths, ranging from plant height, number, width, and leaf color. One of the differences that occur in the growth of kale is caused by the nutrients obtained from catfish that do not meet the needs of kale. The height of the kale also affects the color of the leaves, which causes some of the kale leaves to turn yellow.